PENGARUH KUALITAS AUDIT, OPINI AUDIT TAHUN SEBELUMNYA, AUDIT TENURE, UKURAN PERUSAHAAN, LIKUIDITAS DAN LEVERAGE TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Mardhiah, Oya; Mursidah; yunina; Indrayani (Faculty of Economics and Business, Universitas Malikussaleh, 2025)
This study aims to examine the effect of audit quality, previous year's audit opinion, audit tenure, company size, liquidity and leverage on going concern audit opinion in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this study amounted to 228 companies. The sampling technique used purposive sampling to obtain 141 company samples with 423 observations. This study is a quantitative study using secondary data collected using documentation and literature study techniques obtained through the official website of the Indonesia Stock Exchange www.idx.co.id and the official website of each company which was processed using logistic regression analysis using SPSS 26. The results of the study indicate that the audit quality variable, the previous year's audit opinion variable, and the company size variable do not affect the going concern audit opinion. The audit tenure variable has a negative effect on the going concern audit opinion. While the liquidity variable and the leverage variable have a positive effect on the going concern audit opinion.